สมรรถนะการบริหารงานของผู้บริหารสถานศึกษาในยุคดิจิทัล สังกัดอาชีวศึกษาจังหวัดมหาสารคาม - เวียงสมุทร, จตุรภุช; ชนะโยธา, พรทิวา (วารสารการบริหารการศึกษา มมร.วิทยาเขตร้อยเอ็ด; Vol 3 No 3 (2566): กันยายน-ธันวาคม 2566, 2023)
บทความวิจัยนี้มีวัตถุประสงค์ 1) เพื่อค้นคว้าสมรรถนะการบริหารงานในสถานศึกษาในยุคดิจิทัล สังกัดอาชีวศึกษาจังหวัดมหาสารคาม 2) เพื่อเปรียบเทียบสมรรถนะการบริหารงานของผู้บริหารสถานศึกษา ในดิจิทัล สังกัด อาชีวศึกษาจังหวัดมหาสารคาม จำแนกตามตำแหน่ง วุฒิการศึกษา และ ประสบการณ์การทำงาน 3) เพื่อศึกษาข้อเสนอแนะสมรรถนะการบริหารงานของผู้บริหารสถานศึกษาในยุคดิจิทัล สังกัดอาชีวศึกษาจังหวัดมหาสารคาม กลุ่มตัวอย่างได้แก่ ผู้บริหารสถานศึกษา และครูผู้สอนจำนวน 196 คน เครื่องมือที่ใช้ในการวิจัยแบบสอบถาม สถิติที่ใช้ในการวิจัยได้แก่ ค่าเฉลี่ย ร้อยละ ความถี่ และส่วนเบี่ยงเบนมาตรฐาน  สถิติทดสอบค่าที (t-test) และสถิติการวิเคราะห์ความแปรปรวนทางเดียว F-test (One-Way ANOVA) และวิเคราะห์เชิงพรรณนา (Descriptive Analysis)            ผลการวิจัยพบว่า 1) สมรรถนะการบริหารงานของผู้บริหารสถานศึกษาในยุคดิจิทัล สังกัดอาชีวศึกษาจังหวัดมหาสารคาม โดยรวมอยู่ในระดับมาก ด้านที่มีค่าเฉลี่ยสูงสุด ไปต่ำสุด ได้แก่ ด้านที่มีค่าเฉลี่ยสูงสุด ไปต่ำสุด ได้แก่ ด้านการทำงานเป็นทีม รองลงมาคือ ด้านการมุ่งผลสัมฤทธิ์ ด้านการบริการที่ดี ส่วนด้านที่มีค่าเฉลี่ยต่ำสุด คือ ด้านการพัฒนาตนเอง 2) ผลการเปรียบเทียบระดับความคิดเห็นของบุคลากรที่มีต่อสมรรถนะการบริหารงานของผู้บริหารสถานศึกษาในยุคดิจิทัล สังกัดอาชีวศึกษาจังหวัดมหาสารคาม จำแนกตาม ตำแหน่ง ระดับการศึกษา และประสบการณ์การทำงาน ไม่แตกต่างกัน 3) ข้อเสนอแนะสมรรถนะการบริหารงานของผู้บริหารสถานศึกษาในยุคดิจิทัล สังกัดอาชีวศึกษาจังหวัดมหาสารคาม สรุปได้ว่า ผู้บริหารควรมีการนำเทคโนโลยีดิจิทัลมาใช้ในการเผยแพร่ผลงานทางการบริหาร การพัฒนา และความโปร่งใสในการบริหารงาน ให้เป็นที่ประจักษ์ ควรให้บริการด้วยอัธยาศัยไมตรีมีมนุษย์สัมพันธ์ที่ดีผ่านช่องทางติดต่อต่างๆ ที่ผู้รับบริการใช้ในการสื่อสาร เช่น เฟซบุ๊ก, ไลน์, เว็บไซต์ นำเทคโนโลยีมาใช้ในการบริหารจัดการภายในองค์กรเพื่อการพัฒนาขององค์กร และสามารถแชร์หรือทำงานร่วมกันได้ เช่น กูเกิล ด๊อค, กูเกิล ไดร์ และควรค้นหาแหล่งข้อมูลสารสนเทศที่สนับสนุนการทำงาน The objectives of this research were 1) to study the administrative competencies of educational institute administrators in the digital era under vocational education Maha Sarakham Province. 2) to compare the administrative competency of educational institute administrators in digital era under vocational education Maha Sarakham Province, classified by position, educational background, and work experience. 3) to study the recommendation of management competency of educational institute administrators in the digital era under vocational education Maha Sarakham Province. The sample group was 196 administrators and teachers. To study the recommendation of management competency of school administrators. The research tool used in this research was questionnaire. The statistics used were frequency, percentage, average, and standard deviation, (T-test) statistics and F-test (One-Way ANOVA) and Descriptive Analysis statistics. The data collected were analyzed by the computer program, and the statistical devices composed of Frequency, percentage, mean, standard deviation. The hypothesis was tested with t-test, and One-way ANOVA F-test, descriptive analysis            The research results were as follows: 1) Management competencies of school administrators in the digital age under vocational education, Maha Sarakham Province overall, it was at a high level. The aspects with the highest average to the lowest were teamwork, followed by focus on achievement, good service, The aspect with the lowest average was the Self-development. 2) The comparison of the level of opinions of personnel towards the administrative competency of educational institute administrators in the digital age. under vocational education, Maha Sarakham Province, classified by position, education level and work experience were no difference.                        3) Recommendations for administrative competency of educational institute  administrators in the digital age under the Vocational Education Maha Sarakham Province, it can be concluded that administrators should use digital technology to disseminate management results, development and transparency in administration to be evident service, should be provided with courtesy and good human relations through various communication channels that the service recipient uses to communicate such as Facebook, Line, and website, apply technology in internal management for the development of the organization and can share or collaborate such as Google Doc, Google Drive, and should find information resources that support their work.